2002
DOI: 10.1007/bf02982695
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Imatinib Mesylate of a CML Patient in Megakaryoblastic Crisis with Severe Fibrosis

Abstract: The prognosis of patients with chronic myeloid leukemia in blastic crisis (CML-BC) remains extremely poor, and multiagent chemotherapy regimens commonly used to treat acute leukemia offer only short-term benefits. Therefore, the advent of the novel molecularly targeted anticancer agent imatinib mesylate is a breakthrough in CML therapy. We present a CML patient in megakaryoblastic crisis with severe myelofibrosis, who was treated with imatinib at a dosage of 400 mg/day and achieved complete remission together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The therapeutical approach with Imatinib, after the failure of the conventional therapy in our patient, seems to be surprisingly effective as we have obtained a complete hematological and cytogenetic response and a marked reduction of bone marrow fibrosis as also reported by other authors (7). Recently, in 75 patients with blast‐phase CML, a complete hematological response with Imatinib therapy has been reported in 23% whereas a complete cytogenetic response in only 5% (8).…”
Section: Discussionsupporting
confidence: 87%
“…The therapeutical approach with Imatinib, after the failure of the conventional therapy in our patient, seems to be surprisingly effective as we have obtained a complete hematological and cytogenetic response and a marked reduction of bone marrow fibrosis as also reported by other authors (7). Recently, in 75 patients with blast‐phase CML, a complete hematological response with Imatinib therapy has been reported in 23% whereas a complete cytogenetic response in only 5% (8).…”
Section: Discussionsupporting
confidence: 87%
“…1-6). Tissue fibrosis causes disruption of normal organ architecture, and ultimately leads to their dysfunction and failure.…”
Section: Fibrotic Diseases a Therapeutic Challengementioning
confidence: 99%
“…Of particular interest in the present context are results of numerous recent studies demonstrating that the non-receptor kinase c-Abl participates in some of the TGF-β downstream signaling responsible for the development of a profibrotic phenotype response in a variety of cell types. The initial observations leading to this important discovery appeared in the hematologic literature with three reports describing simultaneously a remarkable reduction of bone marrow fibrosis in patients receiving treatment for chronic myelogenous leukemia with the c-Abl inhibitor, imatinib mesylate (14-16)`. Several subsequent studies confirmed the marked improvement in myelofibrosis following imatinib administration.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Although imatinib provides high complete cytogenetic response (CCyR) and major molecular response (MMR) rates to CML patients, the accumulation of clinical information on imatinib-treated patients has identified patients with treatment failure or suboptimal response [4]. Furthermore, imatinib monotherapy and the combination of imatinib and chemotherapy have also improved the hematological response in patients with CML in BC (CML-BC), although the response is generally transient [3,5,6]. Second-generation BCR-ABL kinase inhibitors, nilotinib and dasatinib, have been approved for clinical use, but their efficacy for CML-BC is also limited [7,8].…”
Section: Introductionmentioning
confidence: 98%